Exploring the relationship of emotional intelligence with mental health among early adolescents - Shabani, Jafar; Hassan, Siti Aishah; Ahmad, Aminah; Baba, Maznah (Canadian Center of Science and Education, 2010)
This study investigates the link of emotional intelligence (EI), with mental health scales and sub-scales (somatic symptom, anxiety, social dysfunction and depression) in Iranian high schools students. The data was made up of 247 high school students of 8 schools (124 Boy and 123 Girl). The research design was a quantitative and tests of alternative hypotheses. This study utilized General Health Questionnaire (GHQ) to measure mental health scales and sub-scales and Emotional Quotient Inventory, Youth Version (EQ-I YV) to assess emotional intelligence. Data analysis included frequencies, percentages, means scores, Pearson’s correlation and, simple regression analysis. The results of this study support the hypothesis that is a significant relationship of emotional intelligence with mental health scales and sub-scales scores. In addition, this study revealed that mental health scales and sub-scales scores influences by emotional intelligence.